2019
DOI: 10.1186/s40246-018-0189-8
|View full text |Cite
|
Sign up to set email alerts
|

The association of functional polymorphisms in genes expressed in endothelial cells and smooth muscle cells with the myocardial infarction

Abstract: BackgroundThe association of platelet endothelial cell adhesion molecule 1 (PECAM1), hypoxia-inducible factor 1 subunit alpha (HIF1A), and KIAA1462 in myocardial infarction (MI) was investigated. The study included 401 Han Chinese MI patients and 409 controls. Three tag single-nucleotide polymorphisms (SNPs)—PECAM1 rs1867624, HIF1A rs2057482, and KIAA1462 rs3739998—were selected. SNP genotyping was performed by an improved multiplex ligation detection reaction assay. A systematic review and meta-analysis of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recent advances in this area have also highlighted a shared mechanistic pathway involving inflammation and endothelium oxidation in endothelial dysfunction (212,213) . For instance, SNPs involved in processes related to endothelial and vascular health such as vascular endothelial growth factor receptor, platelet/endothelial cell adhesion molecule-, endothelial nitric oxide synthase and endothelin-1 contribute to local and systemic vascular disorders (214)(215)(216)(217)(218) , yet studies had small sample sizes, were limited in number or did not account for gene-environment interaction.…”
Section: The Link Between Risk Factors and Endothelial Dysfunction An Intermediary Marker Of Cvdmentioning
confidence: 99%
“…Recent advances in this area have also highlighted a shared mechanistic pathway involving inflammation and endothelium oxidation in endothelial dysfunction (212,213) . For instance, SNPs involved in processes related to endothelial and vascular health such as vascular endothelial growth factor receptor, platelet/endothelial cell adhesion molecule-, endothelial nitric oxide synthase and endothelin-1 contribute to local and systemic vascular disorders (214)(215)(216)(217)(218) , yet studies had small sample sizes, were limited in number or did not account for gene-environment interaction.…”
Section: The Link Between Risk Factors and Endothelial Dysfunction An Intermediary Marker Of Cvdmentioning
confidence: 99%
“…Liu et al identified five genes (encoding signal-induced proliferation-associated 1, transcription factor 21, SMAD family member 3, FES proto-oncogene, and platelet-derived growth factor receptor alpha) that might modulate CAD risk through human coronary artery smooth muscle cells, with all genes having relevant functional roles in vascular remodeling [5]. Furthermore, Li et al provided additional evidence that a genetic variation in the platelet endothelial cell adhesion molecule 1-encoding gene, namely rs1867624, and hypoxia-inducible factor 1 subunit alpha gene, namely rs2057482, can modulate lipid levels in myocardial infarction patients [6].…”
Section: Introductionmentioning
confidence: 99%